ORGANIZATIONAL OPTIMIZATION THROUGH THE DOUBLE DIAMOND - APPLYING INTERDISCIPLINARITY - Caulliraux, Adriano Amaral; Bastos, Delton Pedroso; Araujo, Robson; Costa, Stella Reis (Brazilian Journal of Operations & Production Management, 2020)
Goal: This article reports a project carried out by the company Respondit that had as its main objective the optimization of the organizational processes of the law firm BastosJuris. As a research question, we highlight: “Will the communion between Design Thinking, Lean Thinking and Process Management generate good project results?”. Design / Methodology / Approach: The methodology used was composed by Design Thinking, Process Engineering and Lean. The engagement with employees through prototyping and co-creation, focusing on productivity improvement and error elimination, seeking process optimization and implementation of a management model through continuous improvement, illustrates only one of the possible trajectories arising from mixed methodologies. In this case, "orchestrated" by the double diamond. Results: The project described had an ROI of 815% during its execution and fostered several new initiatives for those involved. Limitations of the investigation: As there is no similar research in the literature to compare with, it is not possible to induce success based in other initiatives. Practical implications: The research shows practical results of the effectiveness of the methodology used in the interdisciplinary context. We seek to promote and encourage the development of similar new researches that take interdisciplinarity as a guide for organizational success. Originality / Value: With regard to the academic contributions, the present study carried out the empirically and holistically variables linked to sustainable management practices, innovation, strategy and their consequent elements, in convergence with the research agenda of the management field, which focuses on results for individuals (employees) and organizations.